2000
DOI: 10.1006/dbio.1999.9592
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Neural Crest Cells Colonise Aganglionic Hindgut in Vivo but Fail to Compensate for Lack of Enteric Ganglia

Abstract: The vagal neural crest is the origin of majority of neurons and glia that constitute the enteric nervous system, the intrinsic innervation of the gut. We have recently confirmed that a second region of the neuraxis, the sacral neural crest, also contributes to the enteric neuronal and glial populations of both the myenteric and the submucosal plexuses in the chick, caudal to the level of the umbilicus. Results from this previous study showed that sacral neural crest-derived precursors colonised the gut in sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 46 publications
6
125
1
Order By: Relevance
“…The neural tube caudal to somite pair 28 provides neural crest cells that colonize only the postumbilical gut (mid-midgut to anus/cloaca). This sacral neural crest colonizes the post-umbilical gut in a caudocranial direction (Burns et al, 2000;Hearn and Newgreen, 2000;Kapur, 2000). After colonization, the ENS is patterned in two concentric rings of ganglia within the radial axis of the gut.…”
Section: Introductionmentioning
confidence: 99%
“…The neural tube caudal to somite pair 28 provides neural crest cells that colonize only the postumbilical gut (mid-midgut to anus/cloaca). This sacral neural crest colonizes the post-umbilical gut in a caudocranial direction (Burns et al, 2000;Hearn and Newgreen, 2000;Kapur, 2000). After colonization, the ENS is patterned in two concentric rings of ganglia within the radial axis of the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent analysis of the developing gut for the presence of quail cells within the enteric plexuses allowed the origin of ENS cells to be defined to the vagal region of the neural crest, adjacent to somites 1-7, which populates the entire length of the gut, while a second region of the neuraxis, the sacral neural crest, caudal to the 28 th pair of somites, was also shown to contribute cells to the hindgut (Le Douarin andTeillet, 1973, Le Douarin andTeillet, 1974). Although numerous authors have subsequently supported the data concerning the contribution of the vagal NC (Burns et al, 2000, Durbec et al, 1996, Epstein et al, 1994, due to conflicting findings, the precise role of the sacral neural crest in ENS formation remained controversial for many years. Evidence supporting a role for sacral NCC in ENS development came from cell labelling studies that traced the development of sacral NCC in the chick using a monoclonal antibody (NC-1) that binds to migrating NCC (Pomeranz and Gershon, 1990).…”
Section: Enteric Nervous System Precursor Cells Are Derived From the mentioning
confidence: 99%
“…These problems were overcome in a series of more recent studies initiated in the laboratory of Nicole Le Douarin, utilising quail-chick interspecies grafting to selectively label sub-populations of NCC, in conjunction with antibody doublelabelling to identify quail cells and neuronal and glial phenotypes within chick enteric ganglia. The combination of these techniques allowed the spatiotemporal migration pathways of vagal and sacral NCC to be determined, along with the identification of the subsequent phenotypes of crest-derived cells within the gut (Burns et al, 2000, Burns andLe Douarin, 1998;Burns and Le Douarin, 2001). These studies demonstrated that vagal NCC initially accumulated in the caudal branchial arches, then entered the foregut mesenchyme at E3 and migrated in a rostro-caudal direction, colonising the hindgut during E7-9.…”
Section: Sacral Ncc Colonise the Hindgut After It Has Been Colonised mentioning
confidence: 99%
“…14 This cell population is divided into several subpopulations depending of their origin along the anterior-posterior axis of the neural tube: cranial, cardiac, vagal, trunk and sacral. The vast majority of ENS progenitors (also refer to as enteric NCCs) has a vagal origin, 14 although minor contingents are also provided by the sacral region 15 and by NCC-derived Schwann cell precursors within the extrinsic nerves of the developing bowel. 16 In the mouse, enteric NCCs of vagal origin initially colonize the foregut mesenchyme around embryonic day (E) 9.5 and then migrate in the rostrocaudal direction to reach the end of the hindgut by E14.5.…”
Section: Formation Of Enteric Glial Cells From Neural Crest Cellsmentioning
confidence: 99%